Comparison between Traditional Chinese Medicine Constitution and Blood Biochemical Markers Associated with Left and Right Mammary Hyperplasia in Rural Areas of Southwest China. (23rd March 2022) - Liao, Li; Feng, Jiahao; Fu, Xi; Cao, Lifang; Fan, Min; Huang, Cheng; Zhang, Jun; Zhang, Lin; Chen, Peng; You, Fengming
Abstract : Background . Hyperplasia of mammary glands (HMG) is the breast disease with the highest clinical incidence. Many traditional Chinese medicine (TCM) doctors suggest that the treatment of HMG should be based on the left and right breast pain difference. However, these views are based on case reports, and an objective basis has not been established for treatment according to left-side and right-side differences. Methods . We enrolled 150 patients who met the clinical diagnostic criteria of HMG. The incidence bias was determined according to the score difference between bilateral breast pain and mass in patients with HMG. A left group, right group, and bilateral group were included, and TCM constitution was investigated in each group. Blood biochemical indicators were measured for 120 fasting patients. We conducted a network pharmacology study of the key herb qingpi and chenpi, which are used by TCM doctors to treat different lateral HMG. Results . In patients with biased onset of HMG, the results showed that the frequency and constitution score of stagnant blood in the L group were higher than those of the R group, and the frequency and constitution score of phlegm-dampness in the R group were higher than those of the L group. Both the L and R groups had high proportion of stagnant Qi. The results indicated that the concentration of coagulation factor VIII (FVIII) was higher in the L group than that in the R group, and the concentration of lipoprotein a (Lp- α ) was higher in the R group than that in the L group. The results showed that sinensetin and neohesperidin contained in qingpi might interfere with platelet activation, thrombogenesis, prolactin signaling pathway, and atherosclerosis process, in removing "blood stasis" and eventually treating the left-leaning group of HMG patients. Sitosterol and citromitin contained in chenpi could regulate lipid metabolism by interfering with regulation of lipolysis in adipocytes, salivary secretion, estrogen signaling pathway, and thyroid hormone signaling pathway. Chenpi could eliminate "phlegm turbidity" and treat HMG patients in the right-leaning group. Conclusions . We preliminarily confirmed that the clinical pathogenesis of HMG is not a left-right equilibrium and TCM constitution, coagulation function, and lipid metabolism may be used as the objective basis for the difference between the left and right in HMG pathogenesis. For left-sided HMG patients, the doctor can consider qingpi, herb of activating blood and removing stasis, to treat HMG. However, for right-sided HMG, we think doctors should apply herb of activating Qi and eliminating phlegm, such as chenpi.